Trends in Lower Extremity Artery Disease Repair Incidence, Comorbidity, and Mortality: A Danish Nationwide Cohort Study, 1996–2018 - Møller A; Eldrup N; Wetterslev J; Hellemann D; Nielsen HB; Rostgaard K; Hjalgrim H; Pedersen OB (Vascular Health and Risk Management, 2024)
Anders Møller,1,2 Nikolaj Eldrup,3– 5 Jørn Wetterslev,6 Dorthe Hellemann,1,5 Henning Bay Nielsen,7,8 Klaus Rostgaard,9,10 Henrik Hjalgrim,5,9– 11,* Ole Birger Pedersen5,10,12,* 1Department of Anesthesia and Intensive Care, Næstved-Slagelse-Ringsted, Slagelse Hospital, Slagelse, Denmark; 2Department of Anaesthesia and Intensive Care, Copenhagen University Hospital - Bispebjerg and Frederiksberg, Copenhagen, Denmark; 3Department of Vascular Surgery, Rigshospitalet, Copenhagen, Denmark; 4Danish Vascular Registry, Aarhus, Denmark; 5Department of Clinical Medicine, Faculty of Health and Medical Sciences, University of Copenhagen, Copenhagen, Denmark; 6Private Office, Tuborg Sundpark, Hellerup, 2900, Denmark; 7Department of Anesthesia and Intensive Care, Zealand University Hospital Roskilde, Roskilde, Denmark; 8Department of Nutrition, Exercise and Sport, Faculty of Science, University of Copenhagen, Copenhagen, Denmark; 9Danish Cancer Institute, Danish Cancer Society, Copenhagen, Denmark; 10Department of Epidemiology Research, Statens Serum Institut, Copenhagen, Denmark; 11Department of Hematology, Copenhagen University Hospital, Copenhagen, Denmark; 12Department of Clinical Immunology, Zealand University Hospital, Køge, Denmark*These authors contributed equally to this workCorrespondence: Anders Møller, Department of Anesthesia and Intensive Care, Næstved-Slagelse-Ringsted Hospital, Fælledvej 11, Slagelse, DK-4200, Denmark, Tel +45 58 55 92 02, Email dr.andersm@gmail.comBackground: The prevalence of occlusive lower extremity artery disease (LEAD) is rising worldwide while European epidemiology data are scarce. We report incidence and mortality of LEAD repair in Denmark from 1996 through 2018, stratified on open aorto-iliac, open peripheral, and endovascular repair.Methods: A nationwide cohort study of prospective data from population-based Danish registers covering 1996 to 2018. Comorbidity was assessed by Charlson’s Comorbidity Index (CCI). Incidence rate (IR) ratios and mortality rate ratios (MRR) were estimated by multivariable Poisson and Cox regression, respectively.Results: We identified 41,438 unique patients undergoing 46,236 incident first-time LEAD repairs by either aorto-iliac- (n=5213), peripheral surgery (n=18,665) or percutaneous transluminal angioplasty (PTA, n=22,358). From 1996 to 2018, the age- and sex-standardized IR for primary revascularization declined from 71.8 to 50.2 per 100,000 person-years (IRR, 0.70; 95% CI, 0.66– 0.75). Following a 2.5-fold IR increase of PTA from 1996 to 2010, all three repair techniques showed a declining trend after 2010. The declining IR was driven by decreasing LEAD repair due to claudication, and by persons aged below 80 years, while the IR increased in persons aged above 80 years (p interaction< 0.001). LEAD repair was more frequent in men (IRRfemale vs male, 0.78; 95% CI, 0.77– 0.80), which was consistent over calendar time (p interaction=0.41). Crude mortality decreased following open/surgical repair, and increased following PTA, but all three techniques trended towards lower adjusted mortality comparing the start and the end of the study period (MRRaorto-iliac, 0.71; 95% CI, 0.54– 0.93 vs MRRperipheral, 0.76; 95% CI, 0.69– 0.83 vs MRRPTA, 0.96; 95% CI, 0.86– 1.07). Increasing age and CCI, male sex, smoking, and care dependency associated with increased mortality.Conclusion: The incidence rate of LEAD repair decreased in Denmark from 1996 to 2018, especially in persons younger than 80 years, and primarily due to reduced revascularization for claudication. Adjusted mortality rates decreased following open surgery, but seemed unaltered following PTA.Keywords: vascular surgery, critical limb ischemia, claudication, Danish Vascular Registry, Danish National Patient Registry, registers